Zakat Mal dalam Perspektif Hadis Maudhu'iy - Hamzah, Hamzah (Tasamuh: Jurnal Studi Islam, 2019)
One of the major problems that the developing countries face is the lack of state revenues to cover all required expenses. Zakat is completely different from taxes, because it is a direct solution for poor people because it goes with the same type of property from the rich to the poor (not like the most of the poverty reduction programms which go in shape of projects for the poor), also Zakat has its own fixed resources and fixed legal channels of spending. Zakat is considered a form of charity that must be paid from a person`s wealth (when his/her wealth exceeds or reaches a “specific amount” of money (or othertypes of wealth like gold) So when the wealth reaches this level or (the specific amount ) the person who owns this wealth should pay a specific amount for the poor and this amount goes to the poor named Zakat. At the time of prophet Mohamed, he was sending the officials to collect money of Zakat, as it was mentioned for example , when he sent Muaaz Ibnu Jabal to govern Yemen, he ordered him to collect money of Zakat. Also in the time of the second gonernant in Islam (Khalifah). At the time of the third Khalifah Umar, where the state was expanded, Umar still interes ed in collecting Zakat but with a new way in terms of two perspectives, first collecting it from both outward and inward money, second by establishing “a Zakat organization” to be the ideal solution in dealing with Zakat. At the time of umar the revenues of Zakat became a huge amount, until Umar decided to give a salary for The periods after that the governants were not interested so much to collect Zakat by themselves and from the outward and inward money, because total toll became very huge so they decided to leave this mater up to the eligible Muslims to pay their Zakat, but in the later on periods of time the Muslims became less aware by the religious practises so the total toll of Zakat became less than periods of the prophet and Khalifah and not sufficient to satisfy the basic needs of the poor in the Muslim countries. To conclude from that, the best total yield of Zakat was happened when it was collected and distributed through an organization with a great attention from the leader of the state, so this paper will be describe about zakat persepective Hadis Maudu’ in the first time of Islam.